2020
DOI: 10.1037/pag0000451
|View full text |Cite
|
Sign up to set email alerts
|

Change in attitudes toward aging: Cognitive complaints matter more than objective performance.

Abstract: Converging longitudinal research suggests that more negative views on aging predict accelerated cognitive decline. Although conceptually suggested, reciprocal relationships between cognitive functioning and attitudes toward aging have remained less clear empirically. We used the 20-year data from the Interdisciplinary Longitudinal Study of Adult Development (ILSE) to better understand such potential bidirectionality. Drawing on 1,002 baseline participants from 2 age groups, a midlife (M age ϭ 43.7 at baseline)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 66 publications
6
43
0
Order By: Relevance
“…However, ATOA and felt age may also be associated with individuals’ perceptions of AARC, such as perceptions of age-related cognitive changes. A recent longitudinal study showed that more negative ATOA predict greater perceived cognitive decline [ 59 ]. Similarly, individuals with an older felt age perceive more age-related losses in the cognitive domain [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, ATOA and felt age may also be associated with individuals’ perceptions of AARC, such as perceptions of age-related cognitive changes. A recent longitudinal study showed that more negative ATOA predict greater perceived cognitive decline [ 59 ]. Similarly, individuals with an older felt age perceive more age-related losses in the cognitive domain [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, ATOA and felt age may also be associated with individuals' perceptions of AARC, such as perceptions of age-related cognitive changes. A recent longitudinal study showed that more negative ATOA predict greater perceived cognitive decline (Siebert, Braun, & Wahl, 2020). Similarly, individuals with an older felt age perceive more age-related losses in the cognitive domain (Segel-Karpas & Palgi, 2019).…”
Section: Validity Of the Aarc-10 Sf And Aarc-50 Cognitive Functioningmentioning
confidence: 97%
“…The simplified reality becomes the accepted reality by individuals, society and the institutions which comprise it. Indeed it has long been recognised that negative stereotypes of older adults lead to an internalisation of that image by the older person (Levy 2009;Siebert et al 2020) and institutions follow.…”
Section: Institutionalised Ageism or Pragmatic Policymentioning
confidence: 99%